2019
DOI: 10.1093/rheumatology/kez300
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in systemic sclerosis before and after autologous haematopoietic stem cell transplant—a systematic review

Abstract: Objectives In severe rapidly progressive SSc, autologous haematopoietic stem cell transplantation (AHSCT) allows significant improvements in overall and event-free survival. We undertook this study to identify, appraise and synthesize the evidence on health-related quality of life (HRQoL) before and after AHSCT for SSc. Methods We performed a systematic review of the literature, following the Preferred Reporting Items for Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…These results are consistent with the purported positive impact of autologous HSCT on physical HRQoL in patients with SSc, which was reported in a recent systematic review of the literature (18). In that review, the most robust evidence was found to be from the ASTIS and SCOT trials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the purported positive impact of autologous HSCT on physical HRQoL in patients with SSc, which was reported in a recent systematic review of the literature (18). In that review, the most robust evidence was found to be from the ASTIS and SCOT trials.…”
Section: Discussionsupporting
confidence: 92%
“…Our group recently undertook a systematic review of the literature to assess current knowledge of the impacts of autologous HSCT on HRQoL in SSc. We demonstrated a promising improvement in physical HRQoL post–autologous HSCT (18). However, the evidence was limited by the characteristics of the studies, including relatively small sample sizes, lack of details on individual HRQoL domains, and short duration of follow‐up (median 1.25–4.5 years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 years, aHSCT has become a standard of care for early rapidly progressive Systemic Sclerosis (6)(7)(8)(9)(10)(11) and has emerged as a promising treatment modality for severe Multiple Sclerosis (12)(13)(14) and Crohn's Disease (12,15). But patients with rarer diseases, such as BD, have undergone aHSCT based on compassionate use.…”
Section: Introductionmentioning
confidence: 99%
“…However, SHAQ is heavily dependent on a tool developed for arthritis and is often improperly scored, making interpretation of results difficult. It correlates with long-term outcome in SSc 8 and may show improvement after treatments such as autologous stem cell transplantation, 9 but it is not disease specific. A feasible global measure is required, and, once fully validated, the Cochin 17-item Scleroderma Functional scale has real potential as a new PROM for clinical trials and practice.…”
mentioning
confidence: 99%